Vascular plant flora of Kiboko range research station, Kenya. - Ndiang'ui, N. Wa (Texas A&M University, 1983)
The flora of the Kiboko National Range Research Station was systematically sampled and collections made in each major ecological site. Belt transects were laid through the sites to serve as reference points in collection of species over all seasons of the year. Representative specimens were collected and identified making up the list of the flora. The relative abundance, habit and longevity of each species were recorded in the field and this has been compiled to form a checklist. The specimens represented sixty (60) families, two hundred twenty (220) genera, and three hundred seventy-three (373) species. The most widespread families on the Research Station in order of prominence included Poaceae (Era~rostis, Digitaria,Chloris, Brachiaria, Setaria), Fabaceae (Acacia), Compositae, Burseraceae (Commiphora), Combretaceae (Combretum), Cappara ceae, Euphorbiaceae, and Acanthaceae.